Mediação e conciliação nos conflitos agrários: o caso da Fazenda Monjolo, Goiás e o poder simbólico - Pereira, Andréa Figueredo (2021)
It is intended to analyze the performance of the Goianian Judiciary, especially by studying the case of Fazenda Monjolo, and the difficulties encountered in resolving agrarian conflicts through the use of the mediation and conciliation techniques provided for by the CPC. To what extent can the application of civil procedural rules, with principles such as impartiality and autonomy of will, influence the achievement of consensual solutions in agrarian conflicts and what is the participation of the Judiciary in this context? The method of case study and bibliographic review will be used and the objective is to know, from the performance of the Judiciary of Goiás, the cause of the little success in obtaining consensual solutions in agrarian conflicts. The theoretical framework of the “Symbolic Power” brought by Bourdieu will be used. From this theory, we will try to understand the role of the judiciary in the resolution of agrarian conflicts as a possible way of perpetuating the power relations existing in society as well as the form of the legal discourse used in the principles that govern mediation and conciliation. The partial results demonstrate that the mediation and conciliation institutes through the principles of impartiality and the autonomy of wills equally treat the parties without considering the specificity of agrarian conflicts in which there is material inequality of those involved, which makes it difficult to obtain consensual solutions in reason of the imposition of power by the strongest party.